Natural resources for sustainable synthesis of nanomaterials with anticancer applications: A move toward green nanomedicine - Rabiee, Navid; Ahmadi, Sepideh; Iravani, Siavash; Varma, Rajender S (Environmental research, 2023)
Today, researchers have focused on the application of environmentally-benign and sustainable micro- and nanosystems for drug delivery and cancer therapy. Compared to conventional chemotherapeutics, advanced micro- and nanosystems designed by applying abundant, natural, and renewable feedstocks have shown biodegradability, biocompatibility, and low toxicity advantages. However, important aspects of toxicological assessments, clinical translational studies, and suitable functionalization/modification still need to be addressed. Herein, the benefits and challenges of green nanomedicine in cancer nanotherapy and targeted drug delivery are cogitated using nanomaterials designed by exploiting natural and renewable resources. The application of nanomaterials accessed from renewable natural resources, comprising metallic nanomaterials, carbon-based nanomaterials, metal-organic frameworks, natural-derived nanomaterials, etc. for targeted anticancer drug delivery and cancer nanotherapy are deliberated, with emphasis on important limitations/challenges and future perspectives.
Keywords: Cancer nanotherapy; nanostruktury; Nanomedicine; Nanomaterials; Anticancer effects; Neoplasms; Green nanomedicine; nádory; lidé; Biowastes; Targeted drug delivery; nanomedicína; Drug Delivery Systems; Natural Resources; přírodní zdroje; lékové transportní systémy; Nanostructures; Natural resources; Humans